2015
DOI: 10.30955/gnj.001687
|View full text |Cite
|
Sign up to set email alerts
|

Use of cerium oxide (CeO2) nanoparticles for the adsorption of dissolved cadmium (II), lead (II) and chromium (VI) at two different pHs in single and multi-component systems

Abstract: Cerium oxide (CeO2) nanoparticles (NPs) were used for the removal of cadmium (II), lead (II) and chromium (VI) ions in single aqueous solutions and in solutions with mixtures of the three metals. The adsorption studies were carried out at pH 5 and 7 using a systematic factorial experimental design that considered the metal concentration from 1 mg l -1 to 10 mg l -1 and NP concentration from 0.064 g l -1 to 0.640 g l ). Data were fitted to a polynomial function obtaining the best reduced models. The type of sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies also demonstrated the uptake and accumulation of elemental Ce in plant tissues through direct uptake of both CeO 2 NPs and their dissolved ions. ,, Ebbs and colleagues investigated that dietary exposure of Ce from CeO 2 NPs or Ce ion exposed carrots and found that dietary intake of element Ce would not exceed the mean oral reference dose of this element in most realistic cases . However, an emerging topic concerning the CeO 2 NPs plant interactions is to understand the impact of CeO 2 NPs on the fate and transport of coexisting environmental pollutants. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also demonstrated the uptake and accumulation of elemental Ce in plant tissues through direct uptake of both CeO 2 NPs and their dissolved ions. ,, Ebbs and colleagues investigated that dietary exposure of Ce from CeO 2 NPs or Ce ion exposed carrots and found that dietary intake of element Ce would not exceed the mean oral reference dose of this element in most realistic cases . However, an emerging topic concerning the CeO 2 NPs plant interactions is to understand the impact of CeO 2 NPs on the fate and transport of coexisting environmental pollutants. …”
Section: Introductionmentioning
confidence: 99%
“…Cerium-based nanomaterials can also be affected by pH ranges. Contreras et al [31] reported that when cerium-based nanoparticles were used in an aqueous solution then its adsorption capacity was affected for the treatment of chromium and cadmium whereas unaffected in the case of lead treatment.…”
Section: Cerium Based Nanomaterialsmentioning
confidence: 99%
“…Another class of material that has been widely studied as adsorbents is inorganic nanoparticles (iNPs), which exhibit high activity and specificity toward heavy-metal ions. , For example, cerium oxide (CeO 2 ) NPs have exhibited excellent adsorption capacities for the following metal ions in water: Pb­(II) (128 mg/g), Cr­(VI) (122 mg/g), Cd­(II) (93 mg/g), and As­(V) (17 mg/g). Importantly, some iNPs can be easily magnetically retrieved from solution, thus obviating impractical alternatives such as filtering. However, a drawback of iNPs is their tendency to aggregate, which significantly compromises their adsorption efficiency.…”
Section: Introductionmentioning
confidence: 99%